Malabaricone C as natural Sphingomyelin Synthase Inhibitor against diet-induced obesity and its lipid metabolism in mice - Othman, MA; Yuyama, Kohei; Murai, Yuta; Igarashi, Yasuyuki; Mikami, Daisuke; Yasodha Sivasothy, *; Khalijah Awang,; Monde, Kenji (American Chemical Society, 2019)
The interaction between natural occurring inhibitors and targeted membrane proteins could be an alternative medicinal strategy for the treatment of metabolic syndrome, notably, obesity. In this study, we identified malabaricones A–C and E (1–4) isolated from the fruits of Myristica cinnamomea King as natural inhibitors for sphingomyelin synthase (SMS), a membrane protein responsible for sphingolipid biosynthesis. Having the most promising inhibition, oral administration of compound 3 exhibited multiple efficacies in reducing weight gain, improving glucose tolerance, and reducing hepatic steatosis in high fat diet-induced obesity mice models. Liver lipid analysis revealed a crucial link between the SMS activities of compound 3 and its lipid metabolism in vitro and in vivo. The nontoxic nature of compound 3 makes it a suitable candidate in search of drugs which can be employed in the treatment and prevention of obesity.